The fabulous four fish fingers - Beresford, Jason (London: Catnip, 2013)
"After an encounter with a crisp-loving elf, best friends Gary, Bel, Ruby and Morris are given super powers. In their new identities, The Chimp, Nightingale, KangaRuby and Slug Boy, must stop super-scary and super-hairy villains Jumper Jack Flash and The Panteater from stealing all the sweets (and pants) in Tumchester"--Back cover
Keywords: Humorous stories